Effect of Auditory Recognition on the Vocabulary Knowledge of Children with Functional Articulation Disorder - YAN Jiajian; WANG Chengdong; LU Jianliang; LI Yuchang; SHEN Longbin; OU Jianlin; CHEN Zhuoming (康复学报)
ObjectiveTo Observe the impact of auditory recognition function on vocabulary knowledge in children with functional articulation disorder (FAD) and to explore the mechanism of working memory (mainly auditory working memory and visual working memory) in the relationship between the two.MethodsA total of 113 children with FAD who were treated at the Rehabilitation Center of the First Affiliated Hospital of Jinan University from November 2019 to January 2022 were selected, with 2 cases dropped out. Each child underwent auditory recognition function testing, vocabulary knowledge testing, auditory working memory testing, and visual working memory testing. The minimum difference phoneme contrast test was used to evaluate the children's auditory recognition function; Peabody Picture Vocabulary Test (PPVT) was used to assess the children's vocabulary knowledge function; auditory working memory of children was evaluated by digital memory span test; visual working memory of children was evaluated using spatial memory span task test.Results1) Correlation analysis was conducted on total average accuracy of minimum difference phoneme contrast test, PPVT score, digit memory span test and spatial memory span task test. It was found that there was a significant positive correlation between total average accuracy of the minimum difference phoneme contrast test and digit memory span test (P<0.001); there was a significant positive correlation between total average accuracy of the minimum difference phoneme contrast test and performance of spatial memory span task (P<0.001); there was a significant positive correlation between total average accuracy of minimum difference phoneme contrast test and PPVT score (P<0.001). There was a significant positive correlation between digit memory span test and spatial memory span task test (P<0.001); there was a significant positive correlation between digit memory span test and PPVT score (P<0.001); there was a significant positive correlation between spatial memory span task test and PPVT score (P<0.001). 2) Auditory working memory (β=0.322, P<0.001) alone had a significant mediating effect on auditory recognition function and vocabulary knowledge function; visual working memory alone (β=0.389, P<0.001) had a significant mediating effect on auditory recognition function and vocabulary knowledge function.ConclusionAuditory recognition can not only directly affect vocabulary knowledge, but also affect vocabulary knowledge through a separate mediation of auditory working memory and visual working memory. This study complements the research on vocabulary knowledge and function of children with FAD in China, and provides theoretical evidence basis for clinical rehabilitation of vocabulary knowledge and function of children with FAD.